Gower: Principles of Modern Company Law - Paul Davies; Sarah Worthington (London Sweet & Maxwell, 2016)
Gower and Davies is the clearest and most reliable text available to cover the increasingly complex subject of company law. Students, as well as those involved in company law on a day-to-day basis, can turn to Gower and Davies secure in the knowledge that it will be an interesting, thought provoking and above all understandable exposition of both law and practice. Gower deals in a clear and in-depth fashion, concentrated on offering a readable approach to core areas. Where case law rules the day, the treatment is clear and lucid, and while thorough avoids over-academic presentation. Presents the leading text available on company law, providing clarity on what is an increasingly complex subject Covers all key areas of company law by way of a detailed, in-depth analysis Incorporates and discusses the changes brought about by the Companies Act 2006
Keywords: Company law; Law; Textbooks